A recurrent mutation in KCNA2 as a novel cause of hereditary spastic paraplegia and ataxia. Issue 4 (9th September 2016) - Helbig, Katherine L.; Hedrich, Ulrike B.S.; Shinde, Deepali N.; Krey, Ilona; Teichmann, Anne‐Christin; Hentschel, Julia; Schubert, Julian; Chamberlin, Adam C.; Huether, Robert; Lu, Hsiao‐Mei; Alcaraz, Wendy A.; Tang, Sha; et al.
Abstract : The hereditary spastic paraplegias (HSPs) are heterogeneous neurodegenerative disorders with over 50 known causative genes. We identified a recurrent mutation in KCNA2 (c.881G>A, p.R294H), encoding the voltage‐gated K + ‐channel, KV 1.2, in two unrelated families with HSP, intellectual disability (ID), and ataxia. Follow‐up analysis of > 2, 000 patients with various neurological phenotypes identified a de novo p.R294H mutation in a proband with ataxia and ID. Two‐electrode voltage‐clamp recordings of Xenopus laevis oocytes expressing mutant KV 1.2 channels showed loss of function with a dominant‐negative effect. Our findings highlight the phenotypic spectrum of a recurrent KCNA2 mutation, implicating ion channel dysfunction as a novel HSP disease mechanism. Ann Neurol 2016